Knowledge of Native Edible Plants in a Monoculture Plantation-Dominated Landscape. Issue Volume 39:Issues 4(2019) (December 2019) - Parra, Santiago A.; Folchi, Mauricio; Simonetti, Javier A.
The loss of forests is a factor that could account for the loss of local knowledge about edible plants. In Chile, the replacement of native vegetation by monoculture plantations of exotic trees has been the main cause of forest loss in recent times. We assess whether this loss of forests affects knowledge of wild edible plants by conducting household surveys in coastal rural localities in south-central Chile, subject to different degrees of replacement of forests. Based on the extinction of experience concept, we analyzed changes in knowledge of edible plants, as well as their gathering and use, through interviews comprised of freelisting and open-ended questions. Our results suggest that loss of native vegetation leads to a reduction in knowledge and use of native edible plants by the local population, but that this reduction occurs at a slower pace than land-use change. Individuals exposed to abundant native forest cover in the past have greater knowledge of edible plants today.